2021
DOI: 10.3389/fcell.2021.796960
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human iPS Cells Into Sensory Neurons Exhibits Developmental Stage-Specific Cryopreservation Challenges

Abstract: Differentiation of human induced pluripotent stem cells (hiPSCs) generates cell phenotypes valuable for cell therapy and personalized medicine. Successful translation of these hiPSC-derived therapeutic products will rely upon effective cryopreservation at multiple stages of the manufacturing cycle. From the perspective of cryobiology, we attempted to understand how the challenge of cryopreservation evolves between cell phenotypes along an hiPSC-to-sensory neuron differentiation trajectory. Cells were cultivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Firstly, the inclusion of ROCK inhibitor (ROCKi) has several benefits throughout the bioprinting process and during early culture. Cell thawing is a critical point in which the neurons can experience a stress response, and improper thawing protocols can decrease the chances of survival 22 . It is typically recommended to thaw cells, add media, and raise cells to incubator temperature as efficiently as possible 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the inclusion of ROCK inhibitor (ROCKi) has several benefits throughout the bioprinting process and during early culture. Cell thawing is a critical point in which the neurons can experience a stress response, and improper thawing protocols can decrease the chances of survival 22 . It is typically recommended to thaw cells, add media, and raise cells to incubator temperature as efficiently as possible 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The studies in this investigation involved single hiPSCs. When attached to other hiPSCs, significant changes in freezing response were observed (Li et al, 2018;Li et al, 2019;Li et al, 2020;Li et al, 2021). It is possible that attachment to other cells changes the membrane permeability, the partitioning of DMSO and therefore the freezing response.…”
Section: Different Cell Types Have Different Partitioning Propertiesmentioning
confidence: 99%
“…Induced pluripotent cells technology it is suitable for this purpose. Some research groups have previously reported on the use of Raman fingerprinting for identifying differentiating states of human induced pluripotent stem cells (hiPSCs) [16][17][18][19][20]. Naturally, the time course of differentiation of many single cells should be measured using multiple cell line types.…”
Section: Introductionmentioning
confidence: 99%